Evaluasi Kelayakan Bangunan Penahan Sampah pada Sistem Sanitary Landfill: Studi Kasus: TPA Pasir Bajing Kabupaten Garut - Susetyaningsih, Adi; Harsi, Nendi Rustandi (Jurnal Konstruksi, 2024)
Pasir Bajing TPA is the only TPA with a Sanitary Landfill system in Garut Regency. The increasing burden of landfills along with population growth makes the feasibility of the Pasir Bajing landfill interesting to study. This research aims to analyze the technical feasibility of the Pasir Bajing TPA and evaluate the feasibility of waste storage buildings in the Sanitary Landfill system at the Pasir Bajing TPA. The research method used is descriptive evaluative. Data obtained directly through field surveys. The technical feasibility of the landfill was analyzed based on SNI-03-3241-1994, while the feasibility of the waste storage building was analyzed using SNI 03-6154-1999. The research results show that the Pasir Bajing TPA technically does not fully meet the requirements according to SNI-03-3241-1994 because there are no monitoring wells, leachate collection buildings, drainage is not yet effective and a new weigh bridge has been built. The evaluation results of the waste storage building show that in terms of dimensions it meets the criteria of SNI 03-6154-1999. Based on the calculation of the capacity of the waste holding building, it is able to accommodate waste for the next 2 years, however, in terms of strength, it is not suitable because the height of the embankment and the height of the embankment or gabions do not match the strength to hold the embankment in the event of a shock or landslide.